Depressive symptoms in association with sociodemographic factors, family functioning and classroom environment in a Malaysian secondary school population - Siti Raudzah, Ghazali; Azizah, Azhar (International Union of Psychological Science, 2012)
The increasing prevalence of depression among adolescents has sparked concern among many healthcare providers. The objectives of this study were to determine the prevalence of depressive symptoms among secondary school students and their associated factors including socio-demographics, perceived general family functioning, and perceived school environment. Method:A cross sectional survey was employed; 386 students were recruited, aged between 13 to 16-years-old. Stratified random sampling was performed to choose four secondary schools; two schools were from the rural area and another two were from the urban area of the district. Results: The rate of depressive symptoms among secondary school students in this area was quite high (34%). Two sociodemographic characteristics were significantly associated with depression; ethnicity and location. Chinese adolescents were more depressed compared to the Malay and Other Native populations. Students staying in rural areas were less depressed compared to students staying in urban areas. Perceived school environment was also significantly associated with depressive symptoms. Students who were depressed were significantly more likely to perceive that their school environment was less conducive. Gender, family functioning, type of schooling, parental arrangement, number of siblings, birth order, family history of depression, staying with extended family members and area of residence have no significant association with depressive symptoms. Conclusion: Findings in this study highlight that socio-demographic characteristics and school environments should be given consideration in health promotion and intervention programs. Thus, health care professionals should recognize that depression among adolescent may become one of the top public health issues in near future.